Implikasi Biaya Penyelenggaraan Pendidikan dan Latar Belakang Sosial Ekonomi Terhadap Minat Calon Mahasiswa Program Studi Akuntansi STIE La Tansa Mashiro dalam Keberlanjutan Perguruan Tinggi - Siti Mudawanah; Mike Mega Rahayu (Universitas Pendidikan Indonesia, 2023)
This study aims to find out empirically about the effect of the cost of providing education and socio-economic background either partially or jointly on the interest of prospective students of the La Tansa Mashiro Accounting Study Program, but also to find out empirically about the effect of the cost of providing education and background . the socio-economic background of the interest of prospective students in the Accounting Study Program STIE La Tansa Mashiro either partially or together with the study and the effect of the cost of providing education and socio-economic background on the study with the interest of prospective students as an intervention variable. This study uses quantitative descriptive analysis with survey methods and primary data through questionnaires to 83 students as a sample, with an analytical tool, namely SmartPLS Version 3.0 software. The research results and conclusions show that partially the cost of providing education has a significant positive effect on the interest of prospective students and social economic background has no significant effect on the interest of prospective students. Meanwhile, simultaneously the cost of providing education and socio-economic background together have a significant positive effect on the interest of prospective students of the STIE La Tansa Mashiro Accounting Study Program. Partially, the cost of providing education and the interest of prospective students have a significant positive effect on the study, socio-economic background has no significant effect on the study. Simultaneously the cost of providing education, social background and interest of prospective students have a positive effect on study in higher education. It can also be said that, there is a significant positive effect on the implementation of education and socio-economic background on studies with the interest of prospective students as an intervention variable.